Taxonomic revision and cladistic analysis of the genus Metalibitia Roewer, 1912 (Opiliones, Cosmetidae, Cosmetinae) - Coronato-Ribeiro, Amanda; Pinto-Da-Rocha, Ricardo (Zootaxa, 2017)
The genus Metalibitia Roewer, 1912, is revised for the first time, and a cladistic analysis revealed that it is a monophyletic clade. This cosmetid harvestmen genus is restricted to open forests and adjacent vegetational formations in South America (humid Forest, being found mostly in the region of cerrado/chaco/pampas). An identification key for all known species is presented and a new species is described, Metalibitia abuna sp. nov. (type locality: Abunã, Porto Velho, Rondônia, Brazil). Two species, Paralibitia maculata Roewer, 1914 and Labrosa arenosa Mello-Leitão, 1939, are here synonymized under Metalibitia argentina (Sørensen, 1884).